Sistema de ciência, tecnologia e inovação: estudo do sistema municipal de São Carlos (SP) - Martinelli, Marcos Alberto (Universidade Federal de São Carlos, 2014)
This research portrays the empirical observation of the relationship between the local administration of a Brazilian city and the elements that make up the so-called Productive and Innovative Local System (SPIL). The research was conducted in the city of São Carlos, located in the center of São Paulo, which has features geared to the theme Science, Technology and Innovation (ST & I). The research investigated the relationships established between the local secretariat specialized in ST & I and other structures related to the theme (SPIL) could be considered as a reference for local innovation system, with leadership of the municipal administration. The aim was to analyze the progress of relations between science, technology and society, seeking to answer the following research problem: "? There is a municipal system of science, technology and innovation in São Carlos (SP)". The study of the municipal system in Sao Carlos - from the perspective of bottom-up - have the objective a better view and understanding about of the transformations and functioning of the National System of Science, Technology and Innovation. The result indicates the existence of a consolidated municipal system, however, this lacks an institutional governance model capable of providing the necessary support to perennial policies, since these depend the longer time for prove effective.
Keywords: Desenvolvimento social - ciência, tecnologia e sociedade; Sistema local de inovação; Ciência; Tecnologia; Science; Technology; Innovation; OUTROS